2016
DOI: 10.3892/mmr.2016.5825
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inhibition attenuates LPS-induced TLR4 activation in monocyte cells

Abstract: Toll-like receptor (TLR) family are receptors for extracellular or intracellular signaling, such as lipopolysaccharide (LPS), or 12-O-tetradecanoylphorbol-13-acetate. TLR induces the differentiation of human myeloid monocytic-leukemia cells (THP-1) to macrophages. However, the relationship between extracellular or intracellular signaling and the TLR protein level remain to be determined. Using RT-PCR and western blot analysis, the aim of the present study was to determine whether TLR4, a major TLR family membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 16 publications
1
37
1
Order By: Relevance
“…LPS presentation on macrophages may mediate the activation of the NF-κB pathway ( 21 , 22 , 37 ), leading to the generation of pro-inflammatory cytokines, including IL-6 and TNF-α. We determined the phosphorylation status of NF-κB with and without BDB treatment by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS presentation on macrophages may mediate the activation of the NF-κB pathway ( 21 , 22 , 37 ), leading to the generation of pro-inflammatory cytokines, including IL-6 and TNF-α. We determined the phosphorylation status of NF-κB with and without BDB treatment by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we reported that N-tosyl-L-phenylalanine chloromethyl ketone, a specific inhibitor of NF-κB signaling, affects IL-6 production ( 23 ). NF-κB inhibition attenuates TLR4 expression in LPS-treated THP1 monocytes ( 22 ). Choi et al .…”
Section: Discussionmentioning
confidence: 99%
“…LPS-induced aggrecan and collagen II downregulation was inhibited by carthamin yellow through the suppression of the MAPK pathway activation (37). LPS stimulates NF-κB binding in the TLR4 gene promoter, whereas TLR4 expression is blocked by NF-κB inhibitors (31,38). Furthermore, LPS was reported to induce inflammation in acute kidney injury (AKI) by activating the TLR4/NF-κB signaling pathway (39).…”
Section: Overexpression Of Mir-140-5p Inhibits Lipopolysaccharideindumentioning
confidence: 99%
“…139 Toll-Like Receptors (TLRs) are strong activators of the NF-κB intracellular pathway. 140 Activation of TLRs on the cells of the periodontium leads to the overstated release of proinflammatory mediators, which may cause host tissue destruction. 141 TLR4 expression is blocked by the NF-κB inhibitor.…”
Section: Nf-κb Signalingmentioning
confidence: 99%
“…141 TLR4 expression is blocked by the NF-κB inhibitor. 140 Neutralization of the NF-κB pathway might provide a useful therapeutic strategy in periodontitis. 142 PDT reduces inflammatory markers NF-kB and inflammatory cytokines.…”
Section: Nf-κb Signalingmentioning
confidence: 99%